Neuroanatomy from Mesoscopic to Nanoscopic Scales: An Improved Method for the Observation of Semithin Sections by High-Resolution Scanning Electron Microscopy - Rodríguez, José-Rodrigo; Turégano-López, Marta; DeFelipe, Javier; Merchán-Pérez, Angel (Frontiers in Neuroanatomy, 2018)
Semithin sections are commonly used to examine large areas of tissue with an optical microscope, in order to locate and trim the regions that will later be studied with the electron microscope. Ideally, the observation of semithin sections would be from mesoscopic to nanoscopic scales directly, instead of using light microscopy and then electron microscopy. Here we propose a method that makes it possible to obtain high-resolution scanning electron microscopy images of large areas of the brain in the millimeter to nanometer range. Since our method is compatible with light microscopy, it is also feasible to generate hybrid light and electron microscopic maps. Additionally, the same tissue blocks that have been used to obtain semithin sections can later be used, if necessary, for transmission electron microscopy, or for focused ion beam milling and scanning electron microscopy (FIB-SEM).